Research on Optimization Measures of Thermal Environment in Dunhuang Traditional Dwellings in Winter - Benteng Liu, Liwei Liu, Mengyao Li, Zhiwei Yang (Forest Chemicals Review, 1970)
The dwellings in Dunhuang area are a kind of special dwellings that are adapted to the local climate and formed under the cold and arid climate. As the times change, local residents begin to transform traditional dwellings to meet the needs of modern people. Whether the measures used in the transformation are suitable for local traditional dwellings is a question worthy of attention. In this paper, by selecting typical traditional dwellings in Dunhuang area and traditional dwellings spontaneously transformed by residents, the indoor and outdoor thermal environment parameters are measured in winter, and the indoor thermal environment of the two types of dwellings is compared. The indoor thermal environment is poor in winter, so it is necessary to improve and optimize. According to the winter thermal environment of two types of Dunhuang traditional residences, the protection and optimization design measures of building orientation, building space and outer protective structure are respectively proposed. The improved indoor temperature can meet the requirements of energy-saving design specifications. The research results are expected to provide a basis and an effect evaluation mechanism for the thermal environment improvement and optimization design of Dunhuang traditional dwellings.